Optimal integration of photovoltaic and shunt compensator considering irradiance and load changes. (January 2022) - Abdelsattar, Montaser; Hamed, Amal M. Abd El; Elbaset, Adel A.; Kamel, Salah; Ebeed, Mohamed
Highlights: The optimal allocation of PV and DSTATCOM. Cost minimization and net saving maximization. Applying the two recent optimization algorithms for solving the studied optimization problem. Determining the candidate losses based on sensitivity analysis. Studying the annual total cost reduction at different penetration levels. Abstract: This paper introduces an efficient two-stage procedure for assigning the optimal sites and sizes of the photovoltaic-based distributed generator (PV-DG) and distribution static synchronous compensator (DSTATCOM). This procedure is applied for radial distribution network (RDN) under seasonal variations of irradiance and load demand. In the first stage, the voltage loss sensitivity index (VLSI) is utilized to identify the high potential buses for integration of the PV-DG and DSTATCOM while in the second stage, two recent optimization algorithms including the lightning attachment procedure optimization (LAPO) and the equilibrium optimizer (EO) are utilized to identify the best sizes and locations of the PV-DG and DSTATCOM from the candidate nodes. The proposed algorithms are tested on a 118-bus distribution system and the obtained results are compared with the Whale optimization algorithm (WOA) and sine cosine algorithm (SCA). The computational study shows the superiority of the application of the new optimization techniques (LAPO and EO) compared with WOA and SCA. Graphical abstract: Image, graphical abstract